WT1-specific TCRs directed against newly identified peptides install antitumor reactivity against acute myeloid leukemia and ovarian carcinoma. Issue 6 (21st June 2022) - van Amerongen, Rosa A; Hagedoorn, Renate S; Remst, Dennis F G; Assendelft, Danique C; van der Steen, Dirk M; Wouters, Anne K; van de Meent, Marian; Kester, Michel G D; de Ru, Arnoud H; Griffioen, Marieke; van Veelen, Peter A; Falkenburg, J H Frederik; et al.
Abstract : Background: Transcription factor Wilms' tumor gene 1 (WT1) is an ideal tumor target based on its expression in a wide range of tumors, low-level expression in normal tissues and promoting role in cancer progression. In clinical trials, WT1 is targeted using peptide-based or dendritic cell-based vaccines and T-cell receptor (TCR)-based therapies. Antitumor reactivities were reported, but T-cell reactivity is hampered by self-tolerance to WT1 and limited number of WT1 peptides, which were thus far selected based on HLA peptide binding algorithms. Methods: In this study, we have overcome both limitations by searching in the allogeneic T-cell repertoire of healthy donors for high-avidity WT1-specific T cells, specific for WT1 peptides derived from the HLA class I associated ligandome of primary leukemia and ovarian carcinoma samples. Results: Using broad panels of malignant cells and healthy cell subsets, T-cell clones were selected that demonstrated potent and specific anti-WT1 T-cell reactivity against five of the eight newly identified WT1 peptides. Notably, T-cell clones for WT1 peptides previously used in clinical trials lacked reactivity against tumor cells, suggesting limited processing and presentation of these peptides. The TCR sequences of four T-cell clones were analyzed and TCR gene transfer into CD8+ T cells installed antitumor reactivity against WT1-expressing solid tumor cell lines, primary acute myeloid leukemia (AML) blasts, and ovarian carcinoma patient samples. Conclusions: Our approach resulted in a set of naturally expressed WT1 peptides and four TCRs that are promising candidates for TCR gene transfer strategies in patients with WT1-expressing tumors, including AML and ovarian carcinoma.